Reassessment of the Early Triassic trematosaurid temnospondyl Tertrema acuta from the Arctic island of Spitsbergen. Issue 1 (2nd January 2021) - Slodownik, Miriam A.; Mörs, Thomas; Kear, Benjamin P.
ABSTRACT: Trematosaurids were globally distributed Early Triassic temnospondyl amphibians characterized by elongate 'crocodile-like' skulls. Some of the most famous trematosaurid fossils were discovered on the island of Spitsbergen in the Arctic Svalbard archipelago. Among these, the short-snouted trematosaurine, Tertrema acuta, is one of the few taxa represented by virtually complete cranial remains. Unusually, however, the type specimens comprise only natural molds that were historically used to reconstruct three-dimensional casts. Here, we re-assess these restorations using the original impressions to phylogenetically analyze and re-diagnose the taxon. Unexpectedly, our first-hand scores differ markedly from previous literature-sourced interpretations and yield conflicting tree topologies that nest T. acuta with long-snouted lonchorhynchines, thus destabilizing the long-favored sub-division of trematosaurids based on their skull shape. We attribute this result to character state conflict and suggest that the traditional classification of trematosaurids may mask more complex evolutionary relationships, as well as possible trophic partitioning, and eco-morphological plasticity.